Optical asymmetric image encryption using DNA through vortex beam encoding - Sonu Kumar Rao; Rahul Kumar; Naveen K. Nishchal; Ayman Alfalou (Discover Applied Sciences)
Abstract Optical vortex beam has gained much attention in the field of information processing because of its inherent features, such as the infinite number of orthogonal modes. In this paper, we demonstrate optical image encryption based on the deoxyribonucleic acid (DNA) encoding rule through optical vortices. In this scheme, two levels of security are achieved; in the first level, an input image is encrypted using equal modulus decomposition as well as phase truncation and phase reservation approach. Thus, the obtained encrypted image is encoded into a DNA sequence according to the existing DNA encoding rule and then DNA exclusive-OR operation is applied with the DNA sequence of a random key image in order to obtain the ciphertext. In the second level of security, the DNA sequence of the encrypted image is encoded into vortex beams using different orthogonal modes and arranged in the form of optical lattices. This type of encoding rule overcomes the tedious task of manually encoding the vortex beam and also enhances the key space and, hence, the security. Simulation and experimental results support the efficacy of the proposed scheme.